An Empirical Study on the Implementation of the Balanced Scorecard in Information Technology Industries in Chennai and Bangalore - R.Bharathvaj; Dr. T.Sreerekha (International Journal of Engineering and Management Research, 2024)
This empirical study examines the implementation of the Balanced Scorecard (BSC) in the Information Technology (IT) industries of Chennai and Bangalore. The BSC, a widely used strategic management framework, is designed to translate an organization's vision and strategy into actionable objectives by incorporating both financial and non-financial performance measures. Given the knowledge-intensive and rapidly evolving nature of the IT sector, this research investigates how organizations in these prominent technological hubs are utilizing the BSC to enhance business performance, operational efficiency, and strategic alignment. A survey conducted among IT professionals in Chennai and Bangalore indicates that the primary reasons for adopting the BSC include the improvement of business processes, the evaluation of managerial performance, the management of operations, and compliance with industry standards such as ISO certification. The findings further underscore the BSC’s role in informing decision-making, elucidating cause-effect relationships, and aligning employee performance with the broader strategic goals of the organization. However, despite its broad adoption, some challenges remain, particularly in the areas of monitoring managerial productivity and effectively communicating strategic initiatives. Overall, the study concludes that the BSC serves as an essential tool for IT firms in Chennai and Bangalore, enabling them to balance short-term operational objectives with long-term strategic goals, while fostering innovation and effectively managing intangible assets that are vital to sustained success in the IT sector.